ETHICS OF USING SOCIAL MEDIA IN THE QURAN AND HADITH GUIDE - JEJE JAENUDIN (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
Research Objectives: To reveal the ethics of using social media in the guidance of the Qur'an and Hadith. Research Methods: Qualitative. Research Results: Four rules were found in using social media. Namely the scientific rules, the rules of justice, the rules of tabayyun, and the rules of benefit.